Prediction and analysis the causes of increasing an illegal e-taxi in Bangladesh municipalities: A case study of Pabna municipality - Mital Chakma; Md Sohel Rana; Md Ashrafuzzaman Pramanik (International Journal of Crowd Science, 2018)
Purpose - This study aims to find out the causes for an increase in the number illegal E-taxis and the extent of these vehicles in the municipalities of Bangladesh. Design/methodology/approach - Based on extensive literature review and field investigation, a set of questionnaires was developed to explore the actual causes for an increase in the number of illegal E-taxis, where ten predicted hypotheses were tested. Findings - The result proved that the illegal E-taxi is very active in the study area. Besides the socio-economic condition of the commuter, education level of taxi drivers and commuter satisfaction level (safety and comfort) and provision of continuous and door-to-door service system are the main causes for increasing number of E-taxis in the municipality of Bangladesh. Originality/value - Moreover, this study provides an effective thinking on socio-economic condition of drivers and the legalization of illegal E-taxis in the study area.